3. Can Combined Therapy With Teriparatide and Low-Intensity Pulsed Ultrasound (LIPUS) Accelerate Fracture Healing?. Issue 8 (August 2016) - Nozaka, Koji; Shimada, Yoichi; Miyakoshi, Naohisa; Yamada, Shin; Hongo, Michio; Nagasawa, Hiroyuki; Kasukawa, Yuji; Saito, Hidetomo; Kijima, Hiroaki; Tsuchie, Hiroyuki
Abstract : Background: It is an advantage for orthopaedic surgeons to remove an Ilizarov external fixator as early as possible after surgery. Although both teriparatide and low-intensity pulsed ultrasound (LIPUS) have been found to accelerate fracture-healing processes, the effect of the combination of teriparatide and LIPUS in clinical bone fracture management remains unclear. Subjects: From among 721 patients with a lower limb fracture on admission to our department who underwent surgical treatment for a lower limb fracture with an Ilizarov external fixator, 38 patients over 60-year-old were investigated. Patients were either treated with an Ilizarov external fixator alone (IEF alone, n = 20) or an Ilizarov external fixator combined with teriparatide and LIPUS (IEF combination, n = 18). The patients' mean age was 64.1 years (range, 60–79 years) in the IEF alone group and 67.2 years (range, 60–83 years) in the IEF combination group. Teriparatide (20 μg subcutaneous injection daily or 56.5 μg subcutaneous injection once-weekly) and LIPUS (20 min/d) were started immediately after surgery for the IEF combination group in an attempt to accelerate healing of the lower limb fracture with the Ilizarov external fixator. Results: The mean time to union was 111.9 days (range, 94–175 days) for IEF alone and 72.1 days (range, 68–141 days) for the IEF combination; it was significantly shorter with the IEF combination. Bone density (relative to young adult mean, YAM) was 61.3% (range, 38%–82%) for IEF alone and 52.1% (range, 30%–79%) for the IEF combination. The mean AOFAS score was 86.2 (range, 72–100) for IEF alone and 91.2 (range, 82–100) for the IEF combination. Discussion: In elderly patients with lower limb fractures, combined therapy (teriparatide and LIPUS) showed a shorter mean duration of union than the Ilizarov external fixator alone. Combined therapy with teriparatide and LIPUS may become a useful option in the treatment of elderly patients with lower limb fractures.